2018
DOI: 10.4314/wsa.v34i3.180623
|View full text |Cite
|
Sign up to set email alerts
|

Water erosion prediction at a national scale for South Africa

Abstract: Erosion is a major soil degradation problem in South Africa, confronting both land and water resource management throughout the country. Given the increasing threat of soil erosion, a need to improve techniques of estimating the soil-erosion risk at a national scale was identified by the National Department of Agriculture and forms the basic premise of this study. Principles and components of the Revised Universal Soil Loss Equation are applied here since the model combines sufficient simplicity for applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…Although rainfall is the main agent causing soil erosion in the KwaZulu‐Natal and eastern parts of the Eastern production region, intense wind erosion causes significant soil losses in the Eastern and Western production regions (Le Roux et al., 2008). Strong winter winds from July to September are common in both the Western and Eastern regions, whereas strong winds associated with intense thunderstorms occur during summer in all maize production regions.…”
Section: Soil Management For Improved and Sustainable Rainfed Maize Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rainfall is the main agent causing soil erosion in the KwaZulu‐Natal and eastern parts of the Eastern production region, intense wind erosion causes significant soil losses in the Eastern and Western production regions (Le Roux et al., 2008). Strong winter winds from July to September are common in both the Western and Eastern regions, whereas strong winds associated with intense thunderstorms occur during summer in all maize production regions.…”
Section: Soil Management For Improved and Sustainable Rainfed Maize Pmentioning
confidence: 99%
“…Soils are degraded through rigorous soil tillage, maize monoculture, and fallow periods, which are common. Soil organic matter and nutrients are depleted and there is significant soil loss through wind and water erosion (Le Roux, Morgenthal, Malherbe, Pretorius, & Sumner, 2008; Mills & Fey, 2003). Although more sustainable practices have been proposed (Kassam, Mkomwa, & Friedrich, 2016; Smith, Kruger, Knot, & Blignaut, 2017; Swanepoel, Swanepoel, & Smith, 2017), adoption of management practices that limit degradation has been slow (Findlater, Kandlikar, & Satterfield, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous soil erosion mapping and modelling studies, however, indicate that large parts of the Tsitsa River Catchment are severely eroded (Le Roux et al, 2008;Mararakanye & Le Roux, 2012). Nevertheless, the studies provide insufficient information about the sediment yield (SYLD) in the catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive sugarcane cultivation as a mono‐cropping system increases soil degradation (Van Antwerpen, ; Du Preez et al, ). Approximately 85% of the country can be considered as degraded (Garland et al, ) mainly due to soil erosion, which has been identified as a key driver responsible for more than 70% of land degradation of South African soils (Le Roux et al, ; Le Roux, ). As such, there is an urgent need to estimate soil loss and identify problematic areas for improved catchment‐based erosion control and sediment management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As such, there is an urgent need to estimate soil loss and identify problematic areas for improved catchment‐based erosion control and sediment management strategies. To‐date, soil erosion research in the Province of KwaZulu‐Natal has tended to focus on macro‐scale gully erosion, while sheet erosion at varying spatial scales has received little research attention (Beckedahl, ; Le Roux et al, ; Dlamini et al, ). Le Roux et al .…”
Section: Introductionmentioning
confidence: 99%